The effects of armed conflicts on local economic dynamics in the Mopti and Ségou regions of Mali - Mahamadou Bassirou Tangara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Armed conflicts significantly affect the social and economic conditions of societies in turmoil, disrupting the normal functioning of local economies. This study seeks to delve into the repercussions of armed conflicts on the dynamics of local economies in Ségou and Mopti, Mali, since the conflict outbreak in 2012. Employing a case study method, the research utilizes field observations and in-depth interviews with various stakeholders, including residents, displaced individuals, local authorities, former hostages, herders, farmers, traders, officials, and members of non-governmental organizations. The examination of the Ségou and Mopti cases underscores how armed conflicts have disrupted local production processes and curtailed population consumption patterns. Notably, weekly fairs, pivotal for economic exchanges, have been either prevented or abandoned by the populations. Additionally, farms face restrictions, with cultivation prohibition or intentional burning upon maturity. These findings contribute valuable insights into the nuanced effects of armed conflicts, cautioning against oversimplified generalizations derived from more aggregate analyses. The study sheds light on the intricacies of the local responses to conflictinduced economic challenges, offering a deeper understanding of the complexities involved.
Keywords: D47; O12; R11; O55; 330; armed conflicts; Mali; economic dynamics; West Africa; production processes; social impact; economic disruption